2021
DOI: 10.3892/mmr.2021.12492
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl sulfide protects against dilated cardiomyopathy via inhibition of oxidative stress and apoptosis in mice

Abstract: Cytochrome P450 family 2 subfamily E member 1 (CYP2E1) is a member of the cytochrome P450 enzyme family and catalyzes the metabolism of various substrates. CYP2E1 is upregulated in multiple heart diseases and causes damage mainly via the production of reactive oxygen species (ROS). In mice, increased CYP2E1 expression induces cardiac myocyte apoptosis, and knockdown of endogenous CYP2E1 can attenuate the pathological development of dilated cardiomyopathy (DCM). Nevertheless, targeted inhibition of CYP2E1 via t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Such an increase in CYP2E1 expression has previously been demonstrated in hypertension and acute myocardial injury, and a key factor might be the upregulation of MYC (Guan et al, 2019). Clearly, increased expression of CYP2E1, a potent prooxidant factor, may be one of the most important reasons for the development of oxidative stress (Pang et al, 2021) in the myocardium, for which we found evidence in our experiment. It has been shown previously that altered expression of CYP2E1 may be a marker of various pathophysiological factors and conditions in the myocardium.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Such an increase in CYP2E1 expression has previously been demonstrated in hypertension and acute myocardial injury, and a key factor might be the upregulation of MYC (Guan et al, 2019). Clearly, increased expression of CYP2E1, a potent prooxidant factor, may be one of the most important reasons for the development of oxidative stress (Pang et al, 2021) in the myocardium, for which we found evidence in our experiment. It has been shown previously that altered expression of CYP2E1 may be a marker of various pathophysiological factors and conditions in the myocardium.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, an increase in CY-P2E1 expression in the early stages of heart failure development may be an adaptation of the myocardium to the conditions of altered energy exchange pathways, ensuring the preservation of the contractile function of the heart. On the other hand, oxidative stress, which may be caused by increased CYP2E1 expression, is one of the crucial pathological mechanisms in the development of heart disease (Guan et al, 2019;Pang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For protein assay, the brain tissues were, respectively, homogenized in lysis buffer containing RIPA buffer (50 mM Tris; 150 mM NaCl; 1% Triton X-100; 1% sodium deoxycholate; 0.1% SDS, P0013B; Beyotime), a protease inhibitor mixture (87785; Thermo Fisher Scientific), a phosphatase inhibitor cocktail (78420; Thermo Fisher Scientific), and 1 mM phenylmethyl-sulfonylfluoride (PMSF; 36978; Thermo Fisher Scientific) as previously reported ( Pang et al, 2021 ). The proteins in the cell membrane fraction and cytoplasm fraction were extracted using a ProteoExtract Subcellular Proteome Extraction Kit (539790; CALBIOCHEM).…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as previously described (Pang et al, 2021 ). The brain tissue homogenates were separated by SDS–PAGE and electroeluted onto nitrocellulose membranes (Immobilon NC; Millipore).…”
Section: Methodsmentioning
confidence: 99%